Normas de bioseguridad y su influencia en los procedimientos de enfermería en el área de pediatría del Hospital Martín Icaza Babahoyo Los Ríos periodo octubre 2018 abril 2019 - Pacheco Peñafiel, Maria Mercedes (2019)
Biosecurity standards is the set of preventive measures aimed at maintaining control of occupational risk factors from biological, physical or chemical agents, being a model of behavior that aims to achieve functions, techniques and procedures that reduce the risk of health professionals in acquire pathogenic agents and propagate them in their environment.Course objective: To analyze the biosafety norms and their influence in the nursing procedures in the pediatric area of the Martin Icaza Babahoyo Los Ríos Hospital period October 2018 April 2019 Methodology: The deductive and inductive method applied in a qualitative and quantitative way was used, being a field bibliographical and descriptive research. For data collection, the survey was used as a tool through a questionnaire of structured questions. Results: The data was analyzed through the Microsoft Excel program where it was stated that the nursing staff fail to comply with the correct application of the biosafety norms Conclusion: When performing the analysis, it was obtained that despite having knowledge of the biosafety norms, they are not correctly applied by different factors, which leads to multiple occupational risks. Under these antecedents the proposal is to establish a plan of awareness to the personnel that the application of the norms of bioseguridad is the most adapted method to prevent infections in the patients and in the personnel of health.